El clan Chiarini: migración y falsificación de dinero en América del Sur, 1890-1910 - Galeano, Diego (El Colegio de México, A.C., 2021)
By studying the history of a family of Italian immigrants dedicated to the fabrication and circulation of counterfeit money, this article analyzes the connection between immigration and crime in fin de siècle South America. Distancing itself from the historiography that sees this nexus as being a criminalizing discourse of political, legal and medical elites, it suggests another approach: by examining the perspective of the counterfeiters themselves, new questions arise regarding the way in which immigrants related to money on the porous border between legal and illegal strategies of accumulation. The market in counterfeit money was a world of trust and mistrust, transactions and treason, ethnic solidarity and blood ties. Along with the producers, intermediaries and circulators of counterfeit money, there were other key actors such as detectives, diplomats, journalists, merchants and bank employees. These many intersections arise from the article’s primary documentary sources: police reports, newspaper articles and judicial and diplomatic archives from different cities on South America’s Atlantic coast, which document the transnational connections that shaped the rhythms of the counterfeiting business.